2020
DOI: 10.17323/jle.2020.10347
|View full text |Cite
|
Sign up to set email alerts
|

A Pre-Experimental Study on a Process-Genre Approach for Teaching Essay Writing

Abstract: This study explored the feasibility of using a process-genre approach (PGA) for teaching academic writing from the perspective of EFL undergraduates. The sample consisted of 15 students enrolled in a four-year English program at the College of Education in Socotra, Yemen during the academic year 2018-2019. The study followed a pre-experimental design in which a pretest was given to the sample, and an extensive 30-hours program was pursued using the PGA. Additionally, ten informants were singled out for intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…The process-genre approach as a hybrid approach is considered capable by experts in developing students' writing skills. Learning to write is the most difficult stage of language learning which requires effective methods, one of which is by combining several approaches (Bin-Hady et al, 2020;Kondal, 2020;Rusinovci, 2022). That is, the process-genre approach is a synthesis of two approaches that help students master writing skills from various aspects, including aspects of organization, vocabulary, grammar, and mechanics (Agesta & Cahyono, 2017;Hoa, 2022;Xu & Li, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The process-genre approach as a hybrid approach is considered capable by experts in developing students' writing skills. Learning to write is the most difficult stage of language learning which requires effective methods, one of which is by combining several approaches (Bin-Hady et al, 2020;Kondal, 2020;Rusinovci, 2022). That is, the process-genre approach is a synthesis of two approaches that help students master writing skills from various aspects, including aspects of organization, vocabulary, grammar, and mechanics (Agesta & Cahyono, 2017;Hoa, 2022;Xu & Li, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many students face challenges when they want to express thoughts in a foreign language, particularly in compositions because writing is a complex skill which demands the use of multifarious tenses and grammatical rules. Semantically, adverbs are effective linguistic tools or strategies which are crucial in the process of generating meaning in discourse (Al-Ahdal et al, 2014;Algamal et al, 2021;Bin-Hady et al, 2020;Hazem & Kanaan, 2020). Yet, there are also some other concepts which are concerned more with syntax and semantics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results indicated that there was a lack of understanding of the the difference between Arabic and English underlying systems and the cultural variations between that the two language possess. To avoid above mentions problems, it is benefitable to think about other teaching strategies like process genre approach, (Bin-Hady et al, 2020) where students get time to practise the writing process and get feedback from teachers.…”
Section: Prepositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The students’ performance with the BBCB was compared to that in the conventional FTF learning environment. The specific focus was on the students’ achievements in writing—the most difficult and challenging skill that students need to master for their learning, career, and daily communication ( Bruning and Horn, 2000 ; Al-Shourafa, 2012 ; Miftah, 2015 ; Mantra, 2017 ; Pertiwi and Drajati, 2018 ; Gunantar and Transinata, 2019 ; Bin-Hady et al, 2020 ; Miftah and Syafii, 2020 ; Syafii and Miftah, 2020 ). What makes acquisition of writing skills a particular challenge is that mastering writing requires the development of multiple micro-skills, such as identification of topic statement, writing supporting details, reviewing, editing, and so forth ( Ahmed, 2020 ).…”
Section: Introductionmentioning
confidence: 99%